The School of Museology Celje: Regular, Continuous, Topical, Quality Form of Education (Cadernos de Sociomuseologia, 2012)
At the School of Museology, a project with ten years of tradition, we carry out module-based programmes to educate and qualify different target audiences working in the filed of cultural heritage. Our development and realization of educational programmes and training courses directed at practical applicability, including life-long learning of adults, topic complementarity with related professional and scientific fields, connection with universities offering undergraduate and postgraduate studies of heritages, promotion of theoretical museological discourses raising awareness of the meaning of cultural heritage, firm placement in an international network of related institutions and promotion of international relations with special emphasis on neighbouring countries. We encourage project partnership and cooperate with different domestic and foreign associates in forming and carrying out programmes.